The Impact of Depression on Employment of Older Workers in Europe - Knebelmann, Justine (OECD Social, Employment and Migration Working Papers, 2016)
According to the World Health Organization, depression is the highest ranking cause of disease in middle- and high income countries; it costs Europe around EUR 118 billion a year, mostly through lost productivity on the labour market, i.e. labour supply loss, sickness absence, and poor performance at the workplace. Using data from waves 1, 2 and 4 of the Survey of Health, Ageing and Retirement in Europe (SHARE), this paper seeks to assess the magnitude of the impact of depression on labour market outcomes of older workers, a population sub-group whose participation in the labour market is ever more crucial in view of rapid population ageing. For each of the studied outcomes, analyses show a substantial impact of depression, measured with the European Depression Scale. Using different methods to address endogeneity this paper finds that depression decreases the probability of being employed by 22 to 51 percentage points among the 50 to 64 year old age group. Older workers with the most symptoms are more than twice as likely as others to exit employment before retirement age. Finally, depression increases annual sickness absence duration by 7.2 days on average. These figures show the necessity for national and firm-level employment policies and programmes targeting the 50 and over population to include prevention of depression, increased awareness of depression and adequate medical support